Extraction optimization and quality evaluation of humic acids from lignite using the cell-free filtrate of Penicillium ortum MJ51. Issue 1 (23rd December 2021) - Li, Shiying; Tan, Jinfang; Wang, Yi; Li, Peipei; Hu, Desheng; Shi, Qiuzhe; Yue, Yanjun; Li, Fang; Han, Yanlai
Abstract : Bio-solubilization of lignite is a promising technology to transform coal into humic acids (HAs) which are broadly used in agriculture. Abstract : Bio-solubilization of lignite is a promising technology to transform coal into humic acids (HAs) which are broadly used in agriculture. In this work, HAs were extracted from lignite using the cell-free filtrate (CFF) of Penicillium ortum MJ51. The extraction method was optimized using response surface methodology (RSM) based on the interactive effects of nitric acid concentrations, coal loading ratio, extraction temperature and time as input factors, and the absorbance of HAs at 450 nm wavelength as the output response. Under optimized conditions (lignite pretreated with 4.7 N HNO3, coal loading ratio of 4.9%, temperature of 77.3 °C and time of 8.6 hours), the absorbance at 450 nm peaked at 70.28, and the concentration and extraction yield of HAs were 31.3 g L −1 and 63.9%, respectively, which were dramatically higher than those observed for traditional biological methods (0.7 g L −1 and 14.1%, respectively). The qualities of HAs produced under optimized conditions were evaluated and compared with those extracted by the conventional chemical method. The optimized process resulted in better HA quality indices, including lower molecular mass; higher nitrogen; less aromatic carbon; more aliphatic and carboxylic carbon; and higher bioactivity for promoting plant growth. Moreover, the anti-flocculation ability was improved, thereby supporting its applicability in agriculture. Extraction of HAs from lignite using the CFF of P. ortum MJ51 provides a novel technological approach for the efficient conversion of lignite to bio-active HAs.